Prevalence of Metabolic Syndrome (MetS) Among Civil Servants in Jambi City:: Using NCEP/ATP III Criteria - Guspianto, Guspianto; Nadwa, Zafira; Nuriyah; Darmawan, Armaidi; Ekaputri Hz, Tia Wida; Ibnu, Ismi Nurwaqiah; Sari, Puspita (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: The incidence of Metabolic Syndrome (MetS) is an important health problem because it was associated with an increase in cardiovascular disease as the main cause of death. The prevalence of MetS in the world at age > 20 years was 24%, age 50 years was 30% and age > 60 years was 40%, while in Indonesia was 17.5% and one of groups that has most risk factors for MetS is the civil servant (ASN). This study aims to obtain a description of the MetS incidence among ASN in Jambi City. Method: A descriptive quantitative study carried out on 108 ASN from six selected government agencies in Jambi city through multistage random sampling technique. Data collection through physical examination to measure of 5 MetS criteria according to the NCEP ATP-III, namely central obesity, blood sugar, blood pressure, triglycerides, and HDL. Determination of the incidence of MetS if the subject has 3 of the 5 criteria. Result: The results of the analysis obtained that the incidence of MetS to 60.2%, and 3 of MetS indicators that have risk majority namely central obesity (74.1%), blood pressure (66.7%), and HDL (63%). Conclusion: It recommendation to prevent and control risk factors that affect the incidence of MetS through improving communication-information-education (IEC) for ASN to raise awareness and develop Posbindu in the workplace to early detection of MetS risk factors. Keywords: Metabolic syndrome, civil servant, jambi city